A Case of Suicide or Accidental Death Due To Self Stabbing - Rautji, Ravi; Kumar , Avishek (Journal of Indian Academy of Forensic Medicine, 2015)
A twenty-nine year old healthy male, software engineer by profession, had been married for the  past three years. He had a strained relationship with his wife. On the fateful day he had an altercation  with his wife in the evening on some issue. Subsequently, he came to the drawing room and started  having liquor, while his wife was in the bedroom watching TV. After consuming few pegs of liquor he went  to the kitchen and stabbed himself on his left thigh and came back to the drawing room and started  having liquor again. After sometime his wife saw him lying unconscious in the drawing room. He was  immediately taken to a nearby hospital, where he was declared dead on arrival. Cause of death was  hemorrhagic shock due to femoral vessel injury.
Keywords: Stab injury; Haemorrhagic shock; Suicide; Femoral vessels